Hedonic Test of Potato Donuts and Sweet Potato Donuts in an effort to Find Small and Medium Business Opportunities - Fajar Anugrah Subhi; Tatik Sriwulandari; Nisa Rahmaniyah Utami (Universitas Pendidikan Indonesia (UPI), 2022)
In an effort to assist the Indonesian government's programto fulfil a balanced nutritional adequacy in the community,especially the age of children, it is necessary to develop adiversification of food products containing energy sources.Thisisbecausethedevelopmentofconsumptionpatternsforstaple foods (food sources of carbohydrates) in Indonesia isstilldominatedbygrains,especiallyriceandwheat,whilethecontribution of tubers is still low. This study aims to offerchildren's snack products in the form of a popular snack,namely donuts which are generally made from wheat flour.Substitutionofwheatwithtubersintheformofsweetpotatoes and potatoes which have many nutritional valueshigherthanflourwastestedon53elementaryschoolstudents to see their perspective and determine the level ofpreferenceforthetwotypesofdiversificationdonutproducts. The results of the organoleptic test showed thatpotato-based donuts had a higherpreference value thansweet potato donuts, by looking at the average value wherepotatodonutsaresuperiorinflavor,textureandaromacategories The results of calculations through the Kruskal-Wallistestshowedthattherewasnodifferencebetweentheproducts tested from all categories assessed, namely Flavor,Color,TextureandAromawithasignificantvaluesmorethan 0,5. The findings obtained in this study can be used as a basis forcommunityconsiderationstofindsmallandmediumbusinessopportunities,especiallydonutproductsmadefromtuberswithatargetmarketofelementaryschoolstudents.